O trabalhador do terciário: sua representação do cotidiano, do trabalho e da sociedade - Rocha, Maria Tereza Siqueira da (1992)
The researched theme: 'The worker of the tertiary - his representation of the daily life, of work and of society' - is a way to explicit my concrete practice. To understand the tertiary from the viewpoint of the production relations, to unveil the level of the representation, as work the fetish, though the explanations produced and the speech itself of the worker, connected to this area of no material production. One begins by discussing the brazilian conjuncture from thirty to eighty, for understanding the oscillation between nationalism and economic liberalism, between the national development, associated to the foreign capital. Different explanations are studied in this context for the tertiary expansion, throughout the structure of occupations, by its marginal effects and by social division of work, where the development and the underdevelopment find their functionality in the capitalism in a worldwide scale. This study leads us to that all these events of social and economica1 nature reflected not as a mechanic relation, but while an articulation between social-política1 and the economical one. And this indissociability is alive in the representation that the worker makes about his daily life of work and of society, although he cannot perceive and cannot unveil the fetish that in his speech and in his conscientiousness, reveals and masks the reality at the same time.